IMPLEMENTATION OF ISLAMIC COMMUNICATION PRINCIPLES IN FORMING HARMONY IN SOCIAL INTERACTION IN THE COMMUNITY: A QUALITATIVE STUDY OF THE SOCIAL SPACE OF COFFEE SHOP IN BANDA ACEH CITY - Annisa Ariftha; Abdullah Abdullah (Journal Analytica Islamica, 2026)
This article discusses the implementation of Islamic communication principles in social life as an effort to build polite, ethical, and harmonious patterns of social interaction. Islamic communication is not only understood as a process of conveying messages, but also as a social practice based on the values of faith, sharia, and morals. Communication problems in modern society, especially amidst the development of digital media and public interaction spaces, show a tendency to use impolite language, the dissemination of information without verification, and a weakening of moral responsibility in communication. Therefore, this article aims to analyze the concept of Islamic communication, social life, the principles of Islamic communication, and their relevance in building social harmony. This study uses a qualitative-descriptive approach based on library research by reviewing various literature related to Islamic communication, social interaction, social support, and da'wah. The results of the study indicate that the principles of qaulan sadidan, qaulan balighan, qaulan maysuran, qaulan layyinan, qaulan kariman, and qaulan ma'rufan have an important role in forming communication that is correct, effective, easy to understand, gentle, noble, and oriented towards goodness. Furthermore, the role of preachers as communicators, counselors, problem solvers, managers, and entrepreneurs expands the function of Islamic communication in addressing social challenges. Thus, Islamic communication can serve as an ethical and practical framework for building a civilized, tolerant society capable of maintaining the quality of social interactions in the global era.